2021
DOI: 10.3390/su13147900
|View full text |Cite
|
Sign up to set email alerts
|

Sheltered Employment Centres: Sustainability and Social Value

Abstract: Sheltered employment centres are social enterprises where at least 70% of their workers have disabilities. They are a way of helping people with disabilities to work in good working conditions and of allowing disadvantaged people to live a full life. However, some people criticise these businesses for being ghettos where public subsidies are used inefficiently. Our paper aims to test if this criticism is valid by analysing whether these companies provide social and economic value to society in return for publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Looking at economic sustainability separately, it refers to maintaining and protecting scarce natural resources, taking into account and ensuring positive social and environmental outcomes (Cadil et al, 2018 ). If economic sustainability is carried out in the right way, it will guarantee a responsible return on resources in the long term (Segovia-Vargas et al, 2021 ). Therefore, economic sustainability must have a circular effect that will strengthen the economy and society; that is why companies must focus on renewable, reusable and recyclable actions and practices, among others (Rai et al, 2021 ).…”
Section: Literature Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Looking at economic sustainability separately, it refers to maintaining and protecting scarce natural resources, taking into account and ensuring positive social and environmental outcomes (Cadil et al, 2018 ). If economic sustainability is carried out in the right way, it will guarantee a responsible return on resources in the long term (Segovia-Vargas et al, 2021 ). Therefore, economic sustainability must have a circular effect that will strengthen the economy and society; that is why companies must focus on renewable, reusable and recyclable actions and practices, among others (Rai et al, 2021 ).…”
Section: Literature Background and Hypothesis Developmentmentioning
confidence: 99%
“…But what is the relationship between the intensity of social media use by the university students and economic sustainability? According to the study by Segovia-Vargas et al ( 2021 ), economic sustainability ensures economic balance and guarantees long-term income for all. Therefore, if the intensity of social media use is done for work or to generate profits and not for addiction, as in some cases (Latif et al, 2019 ), there may be a positive relationship between these two variables.…”
Section: Literature Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The SROI framework can monetize the social impacts and further consider the appropriate improvement for the case of sustainability (Davies et al, 2020). However, this sophisticated approach needs more data to evaluate the program's sustainability (Segovia-vargas et al, 2021). In response to the research background, this research was used to evaluate the social innovation program rarely found in the scientific paper, especially in the Indonesian case.…”
Section: Introductionmentioning
confidence: 99%